Vitamin K Epoxide Reductase Complex Subunit 1-Like 1 (VKORC1L1) Inhibition Induces a Proliferative and Pro-inflammatory Vascular Smooth Muscle Cell Phenotype - Aksoy, Adem; Al Zaidi, Muntadher; Repges, Elena; Becher, Marc Ulrich; Müller, Cornelius; Oldenburg, Johannes; Zimmer, Sebastian; Nickenig, Georg; Tiyerili, Vedat (Frontiers in Cardiovascular Medicine, 2021)
Background: Vitamin K antagonists (VKA) are known to promote adverse cardiovascular remodelling. Contrarily, vitamin K supplementation has been discussed to decelerate cardiovascular disease. The recently described VKOR-isoenzyme Vitamin K epoxide reductase complex subunit 1-like 1 (VKORC1L1) is involved in vitamin K maintenance and exerts antioxidant properties. In this study, we sought to investigate the role of VKORC1L1 in neointima formation and on vascular smooth muscle cell (VSMC) function. Methods and Results: Treatment of wild-type mice with Warfarin, a well-known VKA, increased maladaptive neointima formation after carotid artery injury. This was accompanied by reduced vascular mRNA expression of VKORC1L1. In vitro, Warfarin was found to reduce VKORC1L1 mRNA expression in VSMC. VKORC1L1-downregulation by siRNA promoted viability, migration and formation of reactive oxygen species. VKORC1L1 knockdown further increased expression of key markers of vascular inflammation (NFκB, IL-6). Additionally, downregulation of the endoplasmic reticulum (ER) membrane resident VKORC1L1 increased expression of the main ER Stress moderator, glucose-regulated protein 78 kDa (GRP78). Moreover, treatment with the ER Stress inducer tunicamycin promoted VKORC1L1, but not VKORC1 expression. Finally, we sought to investigate, if treatment with vitamin K can exert protective properties on VSMC. Thus, we examined effects of menaquinone-7 (MK7) on VSMC phenotype switch. MK7 treatment dose-dependently alleviated PDGF-induced proliferation and migration. In addition, we detected a reduction in expression of inflammatory and ER Stress markers. Conclusion: VKA treatment promotes neointima formation after carotid wire injury. In addition, VKA treatment reduces aortal VKORC1L1 mRNA expression. VKORC1L1 inhibition contributes to an adverse VSMC phenotype, while MK7 restores VSMC function. Thus, MK7 supplementation might be a feasible therapeutic option to modulate vitamin K- and VKORC1L1-mediated vasculoprotection.